(untitled) (Global Journal of Medical Research, 2018)
COPD (Chronic Obstructive Pulmonary Disease) is a chronic progressive disease with airflow obstruction. Exacerbations of COPD are a significant cause of hospital admission and readmission and an important determinant of health related quality of life. Identifying risk factors associated with exacerbations would help prevent deterioration in respiratory function. In our study, a total of 100 patients admitted with acute exacerbations of COPD in a tertiary care hospital were investigated using routine blood investigations and sputum study. Critically ill patients admitted in ICU, immunecompromised patients, those who were not compliant with prescribed home based bronchodilator treatment and in patients with sudden breathlessness due to cause other than AECOPD (Acute Exacerbations of COPD) were excluded from the study. Upon admission, a detailed history including history of previous exacerbations, smoking history, prior recent spirometry results were obtained. The data collected from each patient was analyzed using SPSS for windows, version 20.0. In our study, p value less than 0.05 was taken as significant. We found that 60 cases out of 100 had sputum sample positive for bacterial growth. Pseudomonas was the most common organism followed by H. influenza. We also found that not only respiratory infections are a major cause of exacerbations, but they also lead to higher hospital stay and mortality. Smokers had higher frequency of exacerbations.